Growth, physiology, and stomatal parameters of plant polyploids grown under ice age, present-day, and future CO2 concentrations - Šmarda, Petr (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © 2023 New Phytologist Foundation.